Analisis Faktor-Faktor Yang Mempengaruhi Nilai Tukar Petani Di Provinsi Kalimantan Selatan Tahun 2009-2018 - Kholida Annisa; Ika Chandriyanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to determine the effect of harvested area, inflation, and economic growth on the exchange rate of farmers in South Kalimantan.This research was conducted in South Kalimantan by looking at Harvest Area, Inflation, economic growth and NTP in the period 2009-2018. This research is included in the type of quantitative descriptive research. This study uses secondary data and data analysis used is Multiple Linear Regression Analysis.The results of this study include: Harvest area has negative and significant effect on NTP. Inflation does not have a significant effect on NTP; economic growth has a positive and significant effect on NTP; harvested area, inflation, and economic growth simultaneous have a significant effect on NTP.